English Language Training for Tour Guides on Pasir Panjang Village Komodo Islands: Pelatihan English for Tourism bagi Naturalist Guide di Desa Pasir Panjang Kepulauan Komodo - Waskita, Dana; Saidi, Acep Iwan; Pertiwi, Untari Gunta; Vebriyanti, Evi Azizah; Purwaramdhona, Ananda Bintang (Universitas Lancang Kuning, 2025)
The increasing number of foreign tourist visits to Komodo National Park requires naturalist guides to have good communication skills in foreign languages, especially in English. Therefore, the Media Literacy and Visual Culture Expertise Group held English communication skills training for naturalist guides in Pasir Panjang Village, Komodo Islands. This training uses lecture, discussion, and direct practice methods of speaking English that are tailored to the needs of tour guides. The materials presented include how to communicate effectively with foreign tourists using English and the skills of promoting tourist destinations on social media. The evaluation results of this training showed that most tour guides in Pasir Panjang Village (96.2%) considered the materials presented to improve their knowledge and communication skills in English and all participants (100%) considered the materials presented interesting. Keywords: naturalist guide, English communication, Komodo National Park